(untitled) (International Seven Journal of Multidisciplinary, 2025)
Artificial Intelligence (AI) has emerged as an innovative tool in performance management and employee development, offering significant benefits for companies. AI’s ability to analyze large volumes of performance data provides an objective and continuous view of employee behavior, interactions, and outcomes, generating personalized insights to support human resource management decisions. This eliminates the reliance on subjective and infrequent evaluations, favoring a more accurate and dynamic approach. Moreover, AI facilitates the personalization of employee development by adjusting training plans according to individual needs, accelerating the learning process. As a result, companies are better prepared for the challenges of the labor market. AI is also crucial in eliminating biases in performance evaluations, ensuring that decisions are based on concrete data. However, AI implementation must be carefully planned, with transparency and human oversight, to avoid potential algorithmic failures. Studies such as those by Tong et al. (2021) and Rožman et al. (2022, 2023) demonstrate that when applied correctly, AI can enhance productivity, engagement, and organizational performance. The strategic integration of AI can transform management practices, strengthening the company’s competitiveness and fostering a more efficient and fair work environment.